Decision Making for Partial Carpal Fusions - Bain, Gregory Ian; McGuire, Duncan Thomas (Journal of Wrist Surgery, 2012)
Limited wrist fusions are effective surgical procedures for providing pain relief while preserving motion of the wrist in patients with localized arthritis of the carpus. In deciding which motion-preserving procedure to perform, the etiology of the arthritis, which joints are involved, and which are spared should be determined. The main principle is to fuse the involved joints and to allow motion through the uninvolved joints. In this article, we discuss the various traumatic and nontraumatic conditions causing arthritis of the wrist and the treatment options for those conditions. Common indications for limited wrist fusions include scapholunate advanced collapse and scaphoid nonunion advanced collapse. Options for treating these conditions include three- and four-corner fusions as well as a proximal row carpectomy. This paper discusses which procedures are the most appropriate as well as the outcomes of these procedures. If the basic principles of limited wrist fusions are adhered to, a good outcome can be obtained. The authors' surgical technique and decision-making processes are discussed.
Keywords: carpal fusion; wrist salvage; SLAC wrist; SNAC wrist; Kienböck disease